Analysis of Accountability of Securities to Investors in the Event of Embezzlement of Investment Funds by Securities - Achmad Ricky Dwiandi Adam; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Indonesian capital market laws are regulated in Law Number. 8 of 1995 explains the notion of the capital market is an activity related to securities trading and public offerings between actors and issuers. Securities are financial instruments with a certain value that reflect the ownership of a person or business entity in an asset. An alternative term for securities is securities. Ownership of securities or securities is required to generate a return for the owner, according to the percentage of ownership of the asset. The Financial Services Authority (OJK) released risk management rules for implementing risk management in securities companies that are members of the stock exchange (AB). If they do not comply with this risk management policy, the securities company will be subject to sanctions ranging from a warning to revocation of its business license by the OJK. These rules are contained in POJK Number 6/POJK.04/2021 Concerning the Implementation of Risk Management for Securities Companies Conducting Business Activities as Underwriters and Broker-Dealers of Securities who are Members of the Stock Exchange. Accountability in the event of embezzlement of securities to investors in the event of embezzlement of investment funds by securities based on Regulation NUMBER 6 /POJK.04/2021 will be subject to administrative sanctions and the Financial Services Authority can take certain actions against any party who violates the provisions of the Financial Services Authority Regulation This.